The effect of lean and agile practices on supply chain operational performance in Malaysia manufacturing industry - Lee, Khai Loon; Teh, Xing Qi (Penerbit Universiti Malaysia Pahang, 2021)
This study investigates the influence of lean and agile practices on supply chain operational performance in Malaysia manufacturing industry. The lack of IT flexibility, little information sharing, poor delivery performance, and low product quality affect responsiveness, reliability, agility, and cost of supply chain operational performance Malaysia manufacturing industry. This study has utilized the Resource-Based View (RBV) theory to strengthen the framework of this study. The research objectives in this study are to investigate the effect of lean practices and analyzed the effect of agile practices on supply chain operational performance in Malaysia manufacturing industry. To achieve the research objectives, a quantitative research approach is necessitated. The population of this study is 3626 manufacturing companies in Malaysia. The minimum sample size is 107, suggested by a G-power statistical analysis software. Besides, the cluster random sampling technique is used in sample selection. Furthermore, a total of 550 online questionnaires was distributed by email to the manufacturing industry in Malaysia and received a return of 112 responses from respondents representing a 20.36% response rate. Besides, Smart-PLS 3.0 was chosen as the software used for data analysis. Based on research findings, all of the eight hypotheses were supported. The theoretical and practical implication was presented before, the limitations and recommendations were discussed. In conclusion, lean and agile practices play a significant role in improving supply chain operational performance in the Malaysia manufacturing industry.